1997
DOI: 10.1093/emboj/16.23.7174
|View full text |Cite
|
Sign up to set email alerts
|

Functional crosstalk between exon enhancers, polypyrimidine tracts and branchpoint sequences

Abstract: We recently identified enhancer elements that activate the weak 3' splice site of alpha-tropomyosin exon 2 as well as a variety of heterologous weak 3' splice sites. To understand their mechanism of action, we devised an iterative selection strategy to identify functional pyrimidine tracts and branchpoint sequences in the presence or absence of enhancer elements. Surprisingly, we found that strong pyrimidine tracts were selected regardless of the presence of enhancer elements. However, the presence of enhancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 80 publications
1
28
0
Order By: Relevance
“…After six rounds of selection the randomized region at positions 7-16 downstream of the BP sequence was significantly enriched for uridines (54%) and to a lesser extent cytosines (39%)+ Guanosines and adenosines occurred at 4% and 3% of the positions, respectively+ A similar, but slightly less pronounced pyrimidine enrichment was observed in the study by Buvoli et al+ (1997) over two rounds of selection+ At the 39 end of the randomized insert the pyrimidine rich region was followed by a single highly variable nucleotide and an invariant YAG motif+ Uridine residues are also more common than cytidine residues in pyrimidine tracts of natural introns (Shapiro & Senapathy, 1987) and the uridine content is an important determinant of the ability of the pyrimidine tract to compete for BP selection in a construct containing two polypyrimidine tracts adjacent to identical BP sequences (Coolidge et al+, 1997)+ However, our result indicates that the presence of some cytosines is stimulatory to splicing+ A search for common sequence patterns revealed a high frequency of UCCU motifs+ This sequence strongly resembles the UC 2-3 U motif selected in a U2AF 65 affinity selection experiment (Singh et al+, 1995), suggesting that U2AF 65 binding is an important factor in selection of competing splice sites+…”
Section: Selection Of Polypyrimidine Tracts and 39 Splice Sitessupporting
confidence: 60%
See 2 more Smart Citations
“…After six rounds of selection the randomized region at positions 7-16 downstream of the BP sequence was significantly enriched for uridines (54%) and to a lesser extent cytosines (39%)+ Guanosines and adenosines occurred at 4% and 3% of the positions, respectively+ A similar, but slightly less pronounced pyrimidine enrichment was observed in the study by Buvoli et al+ (1997) over two rounds of selection+ At the 39 end of the randomized insert the pyrimidine rich region was followed by a single highly variable nucleotide and an invariant YAG motif+ Uridine residues are also more common than cytidine residues in pyrimidine tracts of natural introns (Shapiro & Senapathy, 1987) and the uridine content is an important determinant of the ability of the pyrimidine tract to compete for BP selection in a construct containing two polypyrimidine tracts adjacent to identical BP sequences (Coolidge et al+, 1997)+ However, our result indicates that the presence of some cytosines is stimulatory to splicing+ A search for common sequence patterns revealed a high frequency of UCCU motifs+ This sequence strongly resembles the UC 2-3 U motif selected in a U2AF 65 affinity selection experiment (Singh et al+, 1995), suggesting that U2AF 65 binding is an important factor in selection of competing splice sites+…”
Section: Selection Of Polypyrimidine Tracts and 39 Splice Sitessupporting
confidence: 60%
“…In one selection experiment we selected BP sequences from a randomized 15-mer region that were able to support pre-mRNA splicing+ The randomized insert evolved towards a UACUAAC motif during seven rounds of selection, implying that pre-mRNAs with a BP sequence, optimized for base pairing with U2 snRNA, are favored in splicing+ Comparison of the sequence consensus in the individual pools revealed characteristic differences in selection rates of individual positions+ After only one round of selection the conservation was limited to UAA, suggesting that this sequence represents a minimal core branch site+ To go through one round of splicing the BP sequence must participate in base pairing with U2 snRNA and be able to expose a suitable nucleophile for the first transesterification step+ Some of the isolated and experimentally confirmed BP sequences after the first round of selection are only able to form 2-3 regular base pairs with U2 snRNA+ This interaction probably reflects a minimal requirement for base pairing for transesterification to occur+ Interestingly, the adenosine preceding the BP nucleotide is the least important in the UAA motif (See Fig+ 3A,E,F,G), suggesting that some structural flexibility is allowed at this position+ This may also explain the high frequency of branching to position Ϫ1 (relative to the BP) that we and others have observed (Hornig et al+, 1986;Query et al+, 1994;Buvoli et al+, 1997; this report)+ The importance of the BP adenosine and the uridine at the Ϫ2 position bears strong resemblance to the specificity observed for the essential splicing factor SF1 (Berglund et al+, 1997) that is required for the association of U2 snRNP with the pre-mRNA (Kramer, 1992)+ Thus, our data supports a model in which the interaction of SF1 and the base pairing of U2 snRNA with the BP sequence cooperate in the assembly of an active spliceosome+ Early recognition of the BP sequence by SF1 is supported by studies in yeast where it was shown that BBP (the yeast homolog of SF1) recognizes the BP sequence in complex E before entry of U2 snRNA (Berglund et al+, 1997;Pascolo & Séraphin, 1997)+ To be selected during the successive rounds of splicing, the sequence must be able to compete efficiently with the other RNA species in the pool for binding of splicing factors+ Our result suggests that an interaction between U2 snRNA and the pre-mRNA involving up to six Watson-Crick base pairs is an important determinant of the competitive strength of a given BP sequence+…”
Section: The Identity Of Functional Branchpoint Sequencesmentioning
confidence: 73%
See 1 more Smart Citation
“…Splicing enhancers can compensate for either a weak PPT or a weak branch point (23). When regulation of the splice sites selection is required, cells can modulate the production of different mRNAs by differentially expressing SR proteins that bind to splicing enhancer elements.…”
Section: Inhibition Of Edi Skipping By the Elongation Inhibitor Drb Imentioning
confidence: 99%
“…Iterative functional selections have not yet been applied toward a functional definition of ISE or ISS elements, although they have been used to define the binding sites of specific splicing inhibitory factors, e.g., PSI, PTB, and hnRNP A1 (Burd and Dreyfuss 1994;Singh et al 1995;Amarasinghe et al 2001). Iterative selections have been used to define functional polypyrimidine tracts and BP sequences (Buvoli et al 1997;Lund et al 2000). Although these are intronic sequences necessary for splicing, they are considered elements integral to the splicing process rather than enhancers.…”
mentioning
confidence: 99%